CDMA Slotted Aloha Mac Protocol for ABR Traffic Over Satellite Links. - Emhemed, Salem Kriem (2000)
The design of a packet radio network with a large number of terminals and a single hub station involves the use of two basically different types of communication channels and channel architectures. One type of channel is a broadcast channel used to transmit data from the hub station to the terminals. Transmitting data from a single hub station to a large number of terminals (one to many) is a relatively simple problem. This channel architecture is almost always configured in a simple time division multiplexed (TOM) mode. The other type is transmitting data from terminals to a single hub (many to one) which is much more challenging problem. In general the choice of multiple access protocol for a particular application should depend on two primary factors: (1) The traffic characteristic of the data network of interest (2) The state of technology development at the time the network is deployed. In this thesis we investigate the combination of two multiple access schemes, slotted Aloha and DS- CDMA spread spectrum protocol (DS-CDMA slotted Aloha) over LEO satellite link in the uplink from terminals to the satellite. In this protocol the channel is divided into time slots. Each user is assigned a time slot equal to the packet transmission. Prior to transmission each user randomly choose unique code sequence different from other users. After transmission the unsuccessful packets should be re-transmitted after a random time delay. The simulation is done by an OPNET package in the presence of LEO satellite system with non-real time traffic type (ABR traffic). The investigation includes the throughput performance of the DS-CDMA slotted Aloha, Packet loss ratio, and the bit errors in the packet transmission in the presence of MAl, AWGN and the error correction mechanism. The simulation shows high throughput performance is obtained against other conventional narrowband protocols such as pure Aloha and slotted Aloha protocols due to the capability of the spread spectrum technique to increase the channel capacity. The simulation also shows an improvement in the throughput performance by implementing the error correction mechanism.